Evaluate the indefinite integral
∫ ( 1 + cos x ) 3 d x .
Clarification: C denotes the arbitrary constant of integration .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫ ( 1 + cos x ) 3 d x = ∫ ( 1 + 2 cos 2 2 x − 1 ) d x = 8 ∫ cos 6 2 x d x = 8 ∫ ( 2 e 2 x i + e − 2 x i ) 6 d x = 8 1 ∫ ( e 3 x i + 6 e 2 x i + 1 5 e x i + 2 0 + 1 5 e − x i + 6 e − 2 x i + e − 3 x i ) d x = 8 1 ( 3 i e 3 x i + 6 2 i e 2 x i + 1 5 i e x i + 2 0 x − 1 5 i e − x i − 6 2 i e − 2 x i − 3 i e − 3 x i ) + C = 4 1 ( 3 1 sin 3 x + 3 sin 2 x + 1 5 sin x + 1 0 x ) + C = 1 2 1 sin 3 x + 4 3 sin 2 x + 4 1 5 sin x + 2 5 x + C
Nice discovery! This is exactly the reason the integrand is useful, as it allows us to recursively generate coefficients for later powers of trig functions. (Here, you outline the connection between the expansion of cos 6 x and the expansions of cos 3 x and lower powers.)
Problem Loading...
Note Loading...
Set Loading...
The first step is to expand:
∫ ( 1 + cos x ) 3 d x = ∫ cos 3 x + 3 cos 2 x + 3 cos x + 1 d x .
Now, it looks like we can use product-to-sum formulas to obtain cos 2 x = 2 1 + 2 1 cos ( 2 x ) and cos 3 x = 4 3 cos x + 4 1 cos ( 3 x ) . We can then plug these back into the integral:
∫ cos 3 x + 3 cos 2 x + 3 cos x + 1 d x = ∫ 4 1 cos ( 3 x ) + 2 3 cos ( 2 x ) + 4 1 5 cos x + 2 5 d x .
And finally, we can integrate ∫ cos ( n x ) d x = n 1 sin ( n x ) + c for each integer n > 0 . So:
∫ 4 1 cos ( 3 x ) + 2 3 cos ( 2 x ) + 4 1 5 cos x + 2 5 d x = 1 2 1 sin ( 3 x ) + 4 3 sin ( 2 x ) + 4 1 5 sin x + 2 5 x + c .